Overall Effectiveness of a Student Affairs Scholar Practitioner Workshop: A Mixed Methods Study. Issue 4 (7th August 2020) - Strietzel, Jeff; Kaul, Corina R.; Sriram, Rishi
Abstract : The purpose of this study was to explore how a semester-long scholar practitioner workshop influenced student affairs professionals' quantitative research and statistics competency. Participants' professional engagement and perceptions of barriers and motivation to develop as scholar practitioners were also examined. Although barriers to development as scholar practitioners persist within student affairs, participating in the workshop increased the participants' competence as quantitative researchers. Implications for current practice and recommendations for future research are provided.